KAJJAN PEMANENAN TERHADAP KERAPATAN TEGAKAN DI BAGIAN HUTAN ALAM TROPIS PROPINSI LAMPUNG - Wesman Endom; Ishak Sumantri (Jurnal Penelitian Hasil Hutan, 1991)
This  paper  studied  the  logging  impact  on forest  density  in  a forest  concession   in  Province  of  Lampung,   38 sample  plots  were taken consisting  of  22 plots  located  in  virgin/not  yet logged  and  16 located  in logged  over  area.  The  result show  that :1.The  initial potential   of  forest  area  can  be  classified  as moderate,   with  composition   of  commercial   wood  of  Dipterocarpaceae   43.9%, 14.4%  Non  Dipterocarpaceae   and  the rest 41.3%  of  non  commercial   species.  The  average  volume  of  commercial   wood  per  hectare  of diameter  class 50 cm  and  up  ranged  from  6 -  42 m3,    and for  diameter  class 20 -  50 cm  ranged  from   7 -  48 m3  per  hektar.   The forest density  of  those  two  diameter  classes  varied from   4 -  16  trees and  16  -  64 trees per  hektar,   respectively.2.Forest   logging   operation    has   reduced   the   volume    and   number    of   commercial    trees   per   hectare   (Dipterocarpaceae    and   Non Dipterocarpaceae)   at about  50%  and  38%  respectively.Compared  to TPTI  (Indonesian  Selective  Cutting System)  it was found   that this condition  can not meet  the TPTI  requirements  for  nucleus trees for  the next  cutting  cycle.3.The  logging  operation  has caused  the openings  of  land  cover  at about  30.54%  per  ha or similar  to an area 3054 m2  per  ha